THE HIGHER BUSINESS EDUCATION: INTERNATIONAL TRENDS AND EMPLOYERS’ EXPECTATIONS TOWARDS GRADUATES’ SKILLS - Anastassova, L. (PUBLISHINGS of Kostanay State Pedagogical University, 2019)
Тhe paper discusses the major trends in the higher business education in global context and it is based on statistical data from reports of many governmental bodies and international organizations like UNESCO, UNO, British Council, United States Institute for International Education, The UK Department for Higher Education etc. On the other hand the paper examines the employ-yers’opinion about the most important skills they value when they employ young graduates with business higher education and the mismatch between expectations and real situation. This part of the paper is based on analysis of secondary data from various international research on employers’ opinion but on empirical data and conclusions as well from a survey with Bulgarian employers of companies as well from different sectors. The last part of the paper contains conclusions and suggestions for future activities on academic institutional level for improvement of the higher education in Bulgaria.
Keywords: business higher education; employers’ expectations; graduates’skills